Cellulolytic bacteria from Coptotermes curvignathus termite gut isolated from coastal area of Bengkulu, Indonesia - DWITA OKTIARNI; LUSIANA LUSIANA; ANDRIAN MARSUGANDA (Society for Indonesian Biodiversity, 2025)
Abstract. Oktiarni D, Lusiana, Marsuganda A. 2025. Cellulolytic bacteria from Coptotermes curvignathus termite gut isolated from coastal area of Bengkulu, Indonesia. Biodiversitas 26: 3252-3261. The conversion of lignocellulosic biomass into bioethanol addresses both renewable energy production and waste management challenges on a global scale. Utilizing diverse types of biomass is particularly advantageous, as lignocellulosic biomass is not a food source for humans and offers an economically viable alternative for waste processing while also enhancing bioethanol production. As highly social insects, termites degrade cellulosic biomass into glucose with the aid of cellulolytic enzymes produced by bacteria residing in their guts. This research aimed to isolate cellulolytic bacteria suitable for hydrolyzing cellulose biomass into glucose for bioethanol production. Cellulolytic bacteria were isolated from the guts of Coptotermes curvignathus (Holmgren, 1913) termites collected in the coastal area of Bengkulu, a region known for its abundant termite populations. The isolated bacteria were characterized and analyzed using biomolecular assays. The identification of cellulolytic bacterial species was performed through biomolecular techniques, by using the PCR method. Eight isolates of cellulolytic gut bacteria were obtained, and showed cellulolytic activity. The PCR results revealed that the cellulolytic bacteria belonged to the species Bacillus cereus and Bacillus thuringiensis. Eight isolates of cellulolytic gut bacteria that obtained, have potential as a source of microbial cellulases for use in hydrolyzing cellulosic biomass into ethanol production.